Examen especial al proceso contable - financiero y su incidencia en la rentabilidad del hotel D´barros, del cantón Quevedo, año 2013 - Moran Pizco, Diana Maricela (2015)
This research was intended to mainly perform a special test to accounting processes - Financial and its impact on the profitability of Hotel D'Barros, for which the deductive, inductive, analytical, synthetic and descriptive method was used by which it was obtained the documentation necessary for the realization of this objective above, the type of research was documentary and field since it is the way we get the real information of the company, using the techniques of observation and interviews with the people involved for the achievement of this research. So the total population being this of (04) people, who are responsible for the management of the company was taken. In the analysis of the results it was evident that the company has very low profitability due to mismanagement it has run since its inception to the present, also the weaknesses of the company such as not having reflected with a control internal cash affecting services and revenues of the company. It exposed the situation of the Hotel was recommended to change the existing policies in the same plant hire an accountant to determine the reasonableness of accounting processes, implement a system of internal control and audit frequent basis for sound decision-making.